AB0351 Risk Factors of Coronary Artery Stenosis in Patients with Rheumatiod Arthritis. (9th June 2015) - Gerasimova, H.; Kolmakova, D.; Fomicheva, O.; Novikova, D.; Popkova, T.; Karpov, Y.; Nasonov, E.
Abstract : Background: Rheumatoid arthritis (RA) patients (pts) have increased cardiovascular (CV) morbidity and mortality. Coronary angiography (CAG) is the gold standard to identify and assess the degree of coronary artery (CA) involvement. CAD development in RA pts is associated with the accumulation of traditional risk factors and immunological mechanisms. RA therapy may also contribute to CAD development. Objectives: To determine clinical predictors and contribution of anti-rheumatic therapy on development of CA stenosis in RA patients. Methods: This is a prospective study of 63 RA pts (25 men and 38 women, mean age 58 [52; 63] years, with a long history of the disease (10, 5 [7; 23] years), seropositive for IgM rheumatoid factor (RF) (82%) and anti-cyclic citrullinated peptide (ACCP) (58%), with moderate to high clinical disease activity DAS 28 =4, 7 [3, 3; 5, 8]). All pts underwent CA angiography. Pts were divided into two groups: Group (1)- RA pts with significant stenosis (>50%) of at least one CA (n=22), Group (2) – pts without coronary stenosis (n=41). The study compared clinical characteristics and RA therapies in two groups. Results: Groups were comparable in terms of age, disease duration and DAS 28 scores. Males prevailed in Group 1: 15/22 (68%) vs 10/41 (24%) in Group 2 ( p <0, 05). The prevalence of traditional risk factors was similar in both groups: hypertension - 77% and 88%, dyslipidemia - 26% and 33%, diabetes mellitus - 5% and 17%, smoking – 45% and 17%, physical inactivity - 58% and 42%, obesity - 45% and 32% pts in Group 1 and 2, respectively. Serum HDL cholesterol concentrations in Group 1 (1, 2 [1, 0; 1.5]mmol/l) was lower, than in Group 2 (1, 55 [1, 3; 2.0]mmol/l, p =0, 03). CVD incidence was higher in Group 1pts with coronary stenosis, i.e.: history of MI 32% vs 2%; CAD - 77% vs 32% pts with and without CA stenosis, respectively p <0, 05. Carotid artery atherosclerotic plaques were detected in 19% and 16%, thickening of the intima-media - in 53% and 56% pts from Group 1 and 2, respectively, p >0, 05. Patients received the following treatment (Group 1 vs Group 2): methotrexate (MTX) (45% vs 85%), leflunomide (13% vs 7%), sulfasalazine (9% vs 2%), biological therapy (18% vs 20%), glucocorticiods (GCs) (54% vs 54%). There were no differences in almost all drugs dosing regiments, with the only exclusion: MTX doses were somewhat lower in Group 1 (10 [10; 15]mg/week) pts as compared to Group 2 (17, 5 [12; 25] mg/week), p =0, 07). Duration of GCs therapy was higher in Group 1 pts (5, 3 [4; 12] years) vs (3, 1 [1, 5; 8], p <0, 05) Group 2. Conclusions: Male gender, low HDL cholesterol and long-term GCs therapy seem to increase the risk of coronary artery stenosis in RA pts. Disclosure of Interest: None declared